A neutrophil treadmill to decouple spatial and temporal signals during chemotaxis. Issue 2 (20th November 2014) - Aranyosi, Alexander J.; Wong, Elisabeth A.; Irimia, Daniel
Abstract : A system that accomplishes a function analogous to a treadmill at the cellular scale helps decouple the spatial and temporal gradients during neutrophil chemotaxis. Abstract : After more than 50 years of debates, the role of spatial and temporal gradients during cell chemotaxis is still a contentious matter. One major challenge is that when cells move in response to a heterogeneous chemical environment they are exposed to both spatial and temporal concentration changes. Even in the presence of perfectly stable chemical gradients, moving cells experience temporal changes of concentration simply by moving between locations with different chemical concentrations in a heterogeneous environment. Thus, the effects of the spatial and temporal stimuli cannot be dissociated and studied independently, hampering progress towards understanding the mechanisms of cell chemotaxis. Here we employ microfluidic and other engineering tools to build a system that accomplishes a function analogous to a treadmill at the cellular scale, holding a moving cell at a specified, unchanging location in a chemical gradient. Using this system, we decouple the spatial and temporal gradients around moving human neutrophils and find that temporal gradients are necessary for the directional persistence of human neutrophils during chemotaxis. Our results suggest that temporal chemoattractant changes are important during neutrophil migration and should be taken into account when deciphering the signalling pathways of cell chemotaxis.